What is the solution the the following system of equations:
2x + 3y – 4z = -1
x – 2y + 5z = 3
- 4x + y + z = 16
(-2,5,3)
(-3.6, .2, 1.4)
(2,5, -3)
(4, -7, -3)

Respuesta :

Answer:

The solution is (-2, 5, 3)

Step-by-step explanation:

2x + 3y - 4z = -1

2(-2) + 3(5) - 4(3) = -1

-4 + 15 - 12 = -1

-16 + 15 = -1

-1 = -1

x - 2y + 5z = 3

-2 - 2(5) + 5(3) = 3

-2 - 10 + 15 = 3

- 12 + 15 = 3

3 = 3

-4x + y + z = 16

-4(-2) + 5 + 3 = 16

8 + 5 + 3 = 16

16 = 16

Therefore, (-2, 5, 3) is a solution.

2x + 3y - 4z = -1

2(-3.6) + 3(0.2) - 4(1.4) = -1

-7.2 + 0.6 - 5.6 = -1

-12.8 + 0.6 = -1

-12.2 = -1

x - 2y + 5z = 3

-3.6 - 2(0.2) + 5(1.4) = 3

-3.6 -0.4 + 7 = 3

-4 + 7 = 3

3 = 3

-4x + y + z = 16

-4(-3.6) + 0.2 + 1.4 = 16

14.4 + 0.2 + 1.4 = 16

16 = 16

(-3.6, 0.2, 1.4) is not a solution.

2x + 3y - 4z = -1

2(2) + 3(5) - 4(-3) = -1

4 + 15 + 12 = -1

31 = -1

x - 2y + 5z = 3

2 - 2(5) + 5(-3) = 3

2 - 10 - 15 = 3

2 - 15 = 3

13 = 3

-4x + y + z = 16

-4(2) + 5 + -3 = 16

-8 + 5 - 3 = 16

-11 + 5 = 16

-6 = 16

(2, 5, -3) is not a solution.

2x + 3y - 4z = -1

2(4) + 3(-7) - 4(-3) = -1

8 - 21 + 12 = -1

-21 + 20 = -1

-1 = -1

x - 2y + 5z = 3

4 - 2(-7) + 5(-3) = 3

4 + 14 - 15 = 3

18 - 15 = 3

3 = 3

-4x + y + z = 16

-4(4) - 7 - 3 = 16

-16 - 7 - 3 = 16

-26 = 16

(4, -7, -3) is not a solution.

ACCESS MORE